Research on the Development and Joint Improvement of Ceramsite Lightweight High-Titanium Heavy Slag Concrete Precast Composite Slab - Jinkun Sun; Rita Yi Man Li; Tao Jiao; Senping Wang; Chenxi Deng; Liyun Zeng (Buildings, 2022)
Despite the continuous improvement in the research and development of concrete precast composite slab technology, problems like easy cracks and excessive weight at the joints remain. In this study, high-titanium heavy slag was mixed with different kinds of ceramsite to prepare ceramsite lightweight high-titanium heavy slag concrete. The joint of the composite slab was optimized to develop a novel ceramsite lightweight high-titanium heavy slag concrete precast composite slab, hereinafter referred to as “CLHCPCS”. Two CLHCPCS and one ordinary concrete composite slab were prepared. This study analyzed the effects of new materials and improved joints on the flexural capacity and crack resistance of CLHCPCS. It concluded that the density of high-titanium heavy slag concrete with shale ceramsite decreased by 12.0%, and the density of high-titanium heavy slag concrete with fly ash ceramsite decreased by 10.6%. At a 30% dosage of fly ash ceramsite, the compressive strength and splitting tensile strength of concrete reached the maximum. At a 20% dosage of shale ceramsite, the mechanical properties were optimal. Finally, fly ash ceramsite was selected as part coarse aggregate of CLHCPCS. CLHCPCS 1 and 2 demonstrated superior ultimate bearing capacity and crack resistance than ordinary concrete composite slab DBS1, with its ultimate bending capacity test value higher than the average value of ordinary concrete composite slab. ANSYS established the joint model of CLHCPCS for a bending simulation test. The stress and strain distribution of the model and the ultimate bending capacity under the plastic line method were obtained, consistent with theory and experimental analysis results.